PENGARUH BOOK TAX DIFFERENCES DAN TINGKAT UTANG TERHADAP PERSISTENSI LABA (Studi Empiris Pada Perusahaan Sektor Property dan Real Estate yang terdaftar di Bursa Efek Indonesia tahun 2016-2018) - Mishelei Loen, SE., M.Si.; Jessica Putri Diharjo (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
Earnings persistence is one of the estimated value of earnings and an element of earnings relevance. The purpose of this research is to determining the effect of variable book tax differences, and leverage either simultaneously or partially to the variable earning persistence. Book tax differences variable is proxied with temporary differences and permanent differences in fiscal reconciliation. Populations used in this study is property and real estate sector companies listed on the Indonesia Stock Exchange 2016-2018, were entered as the population was registered are 70 companies, then obtained a sample of 18 companies. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 41. Data analysis conducted with multiple regression model with help of software SPSS version 25. Based on the results of this research showed a combination of two variables (book tax differences is proxied with temporary differences and permanent differences, and leverage) can affect the earning persistence 35%, while the rest influenced by other variables outside the research. The results also showed simultaneously Book tax differences variable is proxied with temporary differences and permanent differences an leverage significant effect on earnings persistence. From the partial test results showed that the variables Book tax differences variable is proxied with permanent differences and leverage positive significant effect on earning persistence. Variable Book tax differences variable is proxied with temporary differences  did not have any affect on Earnings Persistence.